T Cell Costimulation Blockade may Prevent Tumour Necrosis Factor alpha Inhibitor-Induced Palmoplantar Pustulosis - Rodenhausen, S.; Dan, D.; Caliezi, G.; Möller, B. (Aktuelle Rheumatologie, 2013)
Palmoplantar pustulosis (PPP) is a known side effect of tumour necrosis factor alpha (TNF-α) blocking agents. In this patient with HLAB27-associated spondyloarthritis, PPP started 6 months after the first exposure to Etanercept and persisted for 15 months in spite of reduced dosing for 6 months, and after discontinuation of TNF blockade and intermittent administration of topical corticosteroids for 9 months. T cell costimulation blockade using recombinant CTLA4-Ig (Abatacept) was started 4 months after stopping Etanercept for the treatment of both the refractory psoriatic skin manifestation and the joint inflammation, which relapsed after cessation of anti-TNF treatment. Only the skin manifestation responded satisfactorily to Abatacept after a delay of 5 months, but under prophylactic continuation of this treatment, it was possible to re-expose the patient to Etanercept again, thereby achieving a prompt remission of arthritis, now for more than 2 years, without a new exacerbation of PPP.
Keywords: TNF-α inhibitor; palmoplantar pustulosis; spondyloarthritis